An Empirical Analysis of AI Related Scientific Knowledge and Technologies To Support Elderly Independent Living - Fei Yuan; Kumiko Miyazaki; Santiago Ruiz-Navas (STI Policy and Management Journal, 2021)
The constant increase of an aging society unveils social and economic problems. Elderly independent living (EIL) is supported by numerous services and technologies that take care of their emotional and physical health. Previous studies have reviewed the potential of Artificial Intelligence (AI) applications to support health care, such as AI robots and intelligent senior well-being support systems. A growing number of scientists and tech companies are working on AI applications to help the elderly independent living. We propose to identify AI technological innovation opportunities when developing AI solutions to help the elderly independent living. The research consists of two steps: 1) Identifying AI solutions to help elderly independent living by implementing scientometric analysis on scientific publications related to AI technologies and the elderly. 2) The review and national-level comparison of the identified AI solutions under the proposed framework of elderly need, supporting function, underlying technologies and scientific knowledge. Based on an analysis of the literature on emerging technology in the third AI Boom, we pinpoint science mapping to grasp the situation of research and development of emerging technologies in various regions, to explore the status of technological and research cooperation, to find out the hot research topics of AI technologies in dealing with the problem of aging, to discover the direction of technological development and innovation opportunities in the future, and to combine with the actual need of EIL for exploring the innovative potential of AI technology. From our analysis we can argue that solutions to support elderly independent living require the integration of knowledge from various disciplines, services and products such as machine learning, sensors, data analysis, IoT, wearable devices, sociology and healthcare.Keywords : Artificial Intelligence, Aging society, Elderly independent living, Scientometric, Network analysis